Economic fluctuations and educational inequalities in premature ischemic heart disease mortality in Argentina - Carlos Marcelo Leveau; Mustafa Hussein; José A. Tapia-Granados; Guillermo A. Velázquez (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: Although mortality from ischemic heart disease has declined over the past decades in Argentina, ischemic heart disease remains one of the most frequent causes of death. This study aimed to describe the role of individual and contextual factors on premature ischemic heart disease mortality and to analyze how educational differentials in premature ischemic heart disease mortality changed during economic fluctuations in two provinces of Argentina from 1990 to 2018. To test the relationship between individual (age, sex, and educational level) and contextual (urbanization, poverty, and macroeconomic variations) factors, a multilevel Poisson model was estimated. When controlling for the level of poverty at the departmental level, we observed inequalities in premature ischemic heart disease mortality according to the educational level of individuals, affecting population of low educational level. Moreover, economic expansion was related to an increase in ischemic heart disease mortality, however, expansion years were not associated with increasing educational inequalities in ischemic heart disease mortality. At the departmental level, we found no contextual association beween area-related socioeconomic level and the risk of ischemic heart disease mortality. Despite the continuing decline in ischemic heart disease mortality in Argentina, this study highlighted that social inequalities in mortality risk increased over time. Therefore, prevention policies should be more focused on populations of lower socioeconomic status in Argentina.